2016
DOI: 10.1128/aem.02824-15
|View full text |Cite
|
Sign up to set email alerts
|

The Connection between Persistent, Disinfectant-Resistant Listeria monocytogenes Strains from Two Geographically Separate Iberian Pork Processing Plants: Evidence from Comparative Genome Analysis

Abstract: The aim of this study was to investigate the basis of the putative persistence of Listeria monocytogenes in a new industrial facility dedicated to the processing of ready-to-eat (RTE) Iberian pork products. Quaternary ammonium compounds, which included benzalkonium chloride (BAC), were repeatedly used as surface disinfectants in the processing plant. Clean and disinfected surfaces were sampled to evaluate if resistance to disinfectants was associated with persistence. Of the 14 isolates obtained from product c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
100
1
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(111 citation statements)
references
References 69 publications
7
100
1
1
Order By: Relevance
“…Mechanisms that facilitate the survival of L. monocytogenes in food processing environments include biofilm formation (Nakamura et al, ; Wang et al, ), acquisition of antimicrobial resistance (Fox et al, ; Ortiz et al, , ), and stress resistance mechanisms (Cabrita et al, ; Lundén et al, ; Ortiz et al, ). L. monocytogenes is a saprophytic soil organism and intracellular pathogen that causes infections via the gastrointestinal route, and is able to survive and grow under a wide range of temperatures and stressful environmental conditions including acid and osmotic stress (Gahan and Hill, ; Milillo et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Mechanisms that facilitate the survival of L. monocytogenes in food processing environments include biofilm formation (Nakamura et al, ; Wang et al, ), acquisition of antimicrobial resistance (Fox et al, ; Ortiz et al, , ), and stress resistance mechanisms (Cabrita et al, ; Lundén et al, ; Ortiz et al, ). L. monocytogenes is a saprophytic soil organism and intracellular pathogen that causes infections via the gastrointestinal route, and is able to survive and grow under a wide range of temperatures and stressful environmental conditions including acid and osmotic stress (Gahan and Hill, ; Milillo et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, nine outbreak investigations from years 1989 to 2016 reported focused and detailed sampling investigations of food processing facilities, taking between 19 and 282 samples when production was stopped in order to find the source of Lm associated with cases of human listeriosis (Acciari et al., ; Awofisayo‐Okuyelu et al., ; Dalton et al., ; Gaul et al., ; Jacks et al., ; McLauchlin, Greenwood, & Pini, ; Salvat, Toquin, Michel, & Colin, ; Wenger et al., ; Winter et al., ). On the other hand, studies evaluating the efficacy of interventions conducted sampling immediately before and after the intervention, but may also have followed up after months or years of production to determine the long‐term effect of plant‐specific interventions, such as employee training, equipment disassembly during sanitation, or a new disinfectant compound or procedure (Eglezos, Thygesen, Huang, & Dykes, ; Lappi et al., ; Lappi et al., ; Ortiz, Lopez‐Alonso, Rodriguez, & Martinez‐Suarez, ).…”
Section: Resultsmentioning
confidence: 99%
“…Poimenidou et al (2016) found that quaternary ammonium compounds were more effective against the biofilm formed on polystyrene as compared to the one formed on stainless steel. In contrast, Ortiz et al (2016) reported the resistance of bacilli to quaternary ammonium compounds caused by the long-term use of those particular disinfectants. In the present study, it was found that sodium hydroxide was the least efficient in eliminating L. monocytoges strains.…”
Section: Discussionmentioning
confidence: 99%